1998
DOI: 10.1046/j.1464-410x.1998.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Piroxicam fast‐dissolving dosage form vs diclofenac sodium

Abstract: Objective  To assess the possible therapeutic effect of 40 mg sublingual piroxicam (fast‐dissolving dosage form, FDDF) compared with intramuscular 75 mg diclofenac, as a reference drug, on acute renal colic in a randomized, double‐blind controlled clinical trial. Patients and methods  Eighty patients were assigned to one of two treatment groups; one received an intramuscular injection with 0.2 mL distilled water and two sublingual tablets of 20 mg piroxicam FDDF, and the other received an intramuscular injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…This study showed that either Voltaren ® or Cataflam ® was effective for pain relief with time. (P<0.0001) This was consistent with the results of other studies for patients with renal colic, [4][5][6][7][8][9][10][11] musculoskeletal injuries, [14][15][16][17][18][19][20][21] and arthritis. 25,26 Systolic blood pressure and pulse rate, which would be influenced by the stress of pain, also showed statistically significant reduction with time.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study showed that either Voltaren ® or Cataflam ® was effective for pain relief with time. (P<0.0001) This was consistent with the results of other studies for patients with renal colic, [4][5][6][7][8][9][10][11] musculoskeletal injuries, [14][15][16][17][18][19][20][21] and arthritis. 25,26 Systolic blood pressure and pulse rate, which would be influenced by the stress of pain, also showed statistically significant reduction with time.…”
Section: Discussionsupporting
confidence: 91%
“…In patients with renal colic, various clinical trials have demonstrated that NSAID are at least comparable to and frequently superior to many narcotics and spasmolytic combinations. [4][5][6][7][8][9][10][11] For patients with musculoskeletal pain such as back pain, soft tissue injury, joint injury and arthritis, NSAID have also been shown to be effective and well tolerated analgesics. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, there is no international standard on the route of NSAID use; both parenteral and oral (PO) routes are used for acute pain relief.…”
Section: Study Design and Methodsmentioning
confidence: 99%
“…Many studies have documented the effectiveness of NSAIDs in the treatment of renal colic [36, 37, 38, 39, 40, 41, 42]. NSAIDs do not have the addictive potential of narcotics, yet provide the same degree of pain relief in some clinical settings.…”
Section: Treatmentmentioning
confidence: 99%
“…A randomized clinical trial evaluated the efficacy of indomethacin, 100 mg rectally, versus 50 mg of the same drug given intravenously and showed that the rectal route was less effective than the intravenous route [41]. In a recent study, Supervia et al [42]compared the therapeutic effect of 40 mg sublingual piroxicam with intramuscular 75 mg diclofenac, as a reference drug, on acute renal colic in a randomized double–blind controlled clinical trial. They concluded that sublingual piroxicam is as effective as parenteral diclofenac in emergency renal colic treatment.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation